Transitive Maps on Topological Spaces - Bilokopytov, E.; Kolyada, S. F. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
In the present paper, we consider the problem of existence of nonequivalent definitions of topological transitivity, which is a classical problem of the topological dynamics. In particular, we use the fact that all available definitions of this kind imply a condition imposed on the dynamical system. The main result of our investigations is the complete classification of these dynamical systems.